Forensic Psychology to Speed Up Recovery of Rape Victims - Patisina, Patisina; Lubis, Suaidah (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study investigates the psychological recovery of rape victims in Indonesia, emphasizing the critical role of forensic psychologists in facilitating healing. Utilizing qualitative and juridical normative methodologies, data were collected through interviews with five key informants, including professionals from the Indonesian Forensic Psychology Association and law enforcement. The findings reveal that victims often experience PTSD, anxiety, and depression, necessitating tailored therapeutic interventions such as Neuro-Linguistic Programming, hypnotherapy, and play therapy. Results indicate that comprehensive support systems, including legal protection and community awareness, are essential for effective recovery. This research contributes to understanding the multifaceted needs of rape victims and underscores the importance of professional psychological assistance in their healing journey.